The impact of drivetrain configuration on overall cycling efficiency: simulations, experiments and case studies from World Tour time trialing - Blockmans, B.; Laseur, S.; de Jong, H.; Verschaeve, V.; De Naeyer, B.; van Druten, R. (Journal of Science and Cycling, 2025)
Despite frequent displays of undisputed dominance in cycling`s biggest road races, time trialing remains a test of precision, where victory is often determined by razor-thin margins. In all of the major time trials of the 2024 season, champions were separated from runners-up by time differences of less than 0.5% (or 9 seconds per 30 minutes). As a consequence, the pursuit of cycling efficiency has never been as relentless as today, with countless hours of wind tunnel testing being used to scrape off the last fraction of a watt from a cyclist`s jersey. Besides aerodynamic efficiency, bicycle drive-train efficiency has received increased interest in recent years. On the verge of what could be a paradigm shift in bicycle drivetrain technology, the traditional front derailleur-based 2x systems are increasingly being challenged by "derailleur-killing" technologies such as 1x configurations and drivetrains equipped with hub gears. Whether or not said technology shift will actually happen, and if so in which of cycling`s many disciplines, depends to a large extend on the proven efficiency of these new drivetrain concepts. In the current work, a comparative analysis of various drivetrain configurations is presented, based on a combined simulation-based and experimental approach, with case studies from World Tour time trialing in the 2024 and 2025 seasons.